Analisis Kemampuan Computational Thinking pada Literasi Saintek Calon Guru untuk Mahasiswa Kependidikan Universitas PGRI Semarang - Huda, Choirul; Reffiane, Fine; Agustini, Ferina; Mudzanatun, Mudzanatun (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2025)
This research focuses on analyzing Computational Thinking Ability in the Scientific and Technological Literacy of Education Students at Universitas PGRI Semarang. Computational Thinking abilities possessed by students are a challenge in the digital era. Students are able to integrate IT and manual learning to form good collaboration. The research method in this study uses a qualitative descriptive method. The research subjects were education students in the Primary School Teacher Education study program at Universitas PGRI Semarang. The success of this research can be seen from 5 indicators: (1) Effectiveness of Computational Thinking Learning in the good category (46.6%), (2) Low Risk of Environmental Damage in Computational Thinking Learning in the good category (39.7%), (3) Computational Thinking Learning using Modern Technology in the good category (43.1%), (4) Computational Thinking Learning Oriented to Problem Solving in the good category (42.9%), (5) Development of Computational Thinking Learning Product Results in the good category (45, 6%)